(untitled) (Journal of Medical & Health Sciences Review, 2025)
Beta-thalassemia is a severe hereditary blood disorder characterized by ineffective erythropoiesis, chronic anemia, and iron overload due to frequent blood transfusions. This study evaluates liver function tests (LFTs), serum vitamin D, calcium, and ferritin levels in 200 pediatric patients (110 males, 90 females) with beta-thalassemia major. The biochemical analysis revealed that 55.5% of patients had elevated AST levels (>40 U/L), 22% had ALT >56 U/L, and 10% exhibited ALP >129 U/L, indicating potential liver damage due to iron overload. A striking 99% of patients had vitamin D deficiency (<20 ng/mL), highlighting a critical issue in thalassemic children despite adequate sunlight exposure. Serum calcium levels were normal in 71% of patients, while 20% had low levels. Ferritin levels ranged from 1000 to 6000 ng/mL in 61% of patients, with a mean value of 4584.78 ng/mL, substantially over normal limits. A substantial association was found between high ferritin levels and vitamin D insufficiency, indicating a link between iron excess and bone metabolism disruptions. These findings highlight the need for enhanced management techniques, such as vitamin D supplements and iron chelation therapy, to reduce liver dysfunction and bone health deterioration in beta-thalassemia patients.